Image analyses of collagen types and thickness in oral sub mucous fibrosis stained with picrosirius red under polarizing microscope - Venkatesh V Kamath; Krishnanand Satelur; Y Komali; Shruthi S Krishnamurthy (Wolters Kluwer Medknow Publications, 2013)
Context: Oral submucous fibrosis (OSF) is a potentially malignant oral disorder leading to increased fibrosis in the sub-epithelial layer. The collagen in the condition has been a subject of intense scrutiny in an attempt to understand the pathogenesis of the disease. Aim: The present study aims to quantify and qualify the collagen fibers in different histological grades of OSF using picrosirius red stain under the polarizing microscope. The quantification of the fibrosis was carried out using image analysis software and the fibers were graded according to staining hue and intensity into their respective subtypes. Comparison was done with normal mucosa, scar/keloid tissue samples. Materials and Methods: The present study included OSF (n = 50) of differing histological grades, keloid/scar (n = 4) and normal mucosa (n = 6) as control cases. Histological assessment was performed on hematoxylin and eosin stained sections. Picrosirius red stained slides were observed under a polarizing microscope for assessment of collagen subtypes. Quantification of collagen was done under polarizing microscope and image parameters were analyzed using ProReg® Capture Pro 2.8.8 (Lawrence and Mayo India Pvt Ltd, 2011) image analysis software. Results: The epithelial thickness in OSF, scar and keloid is less than that of normal mucosa and progressive decrease in the epithelial thickness is seen in the successive stages of OSF. The fibrosis increases with increasing grades of OSF, was higher in scar and keloid and was highly statistically significant. Type I collagen was more predominant in all stages of OSF, in normal oral mucosa and scar/keloid tissue samples as compared with type III. Though quantitative analysis of the collagen types I and III is possible, with picrosirius red qualitative analysis is an arduous task. The specificity of detection of collagen subtypes was acceptable with the picrosirius red stain, but the sensitivity left a lot to be desired.